Stemming the Standard-of-Care Sprawl: Clinician Self-Interest and the Case of Electronic Fetal Monitoring - Spector-Bagdady, Kayte (The Hastings Center report, 2017)
The “best interests of the patient” standard—a complex balance between the principles of beneficence and autonomy—is the driving force of ethical clinical care. Clinicians’ fear of litigation is a challenge to that ethical paradigm. But is it ever ethically appropriate for clinicians to undertake a procedure with the primary goal of protecting themselves from potential legal action? Complicating that question is the fact that tort liability is adjudicated based on what most clinicians are doing, not the scientific basis of whether they should be doing it in the first place. In a court of law, clinicians are generally judged based on the “reasonably prudent” standard: what a reasonably prudent practitioner in a similar situation would do. But this legal standard can have the effect of shifting the medical standard of care—enabling a standard-of-care sprawl where actions undertaken for the primary purpose of avoiding liability reset the standard of care against which clinicians will be adjudicated. While this problem has been recognized in the legal literature, neither current ethical models of care nor legal theory offer workable solutions. One of the best examples of the conflict between evidence-based medicine and common clinical practice is the use of electronic fetal monitoring. Despite strong evidence and professional guidelines that argue against the use of EFM for healthy pregnancies, the practice persists. One of the main reasons for this is often assumed to be physicians’ concerns about liability.